2018
DOI: 10.1016/j.exer.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on mitochondria, axonal transport, and axonal degeneration after chronic IOP elevation using a murine ocular explant model

Abstract: The purpose of this study was to compare younger and older mice after chronic intraocular pressure (IOP) elevation lasting up to 4 days with respect to mitochondrial density, structure, and movement, as well as axonal integrity, in an ex vivo explant model. We studied 2 transgenic mouse strains, both on a C57BL/6J background, one expressing yellow fluorescent protein (YFP) in selected axons and one expressing cyan fluorescent protein (CFP) in all mitochondria. Mice of 4 months or 14 months of age were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…R1 is also the region where axonal transport is blocked in mice. 7 , 39 41 Similarly, in larger mammalian eyes and humans, transport block in axons occurs in the connective tissue zone of the LC and myelination begins just posterior to this. 3 , 42 – 44 The accumulation of amyloid precursor protein 33 during axonal obstruction can lead to axonal swelling, 39 , 45 resulting in the increase in axonal area measured in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R1 is also the region where axonal transport is blocked in mice. 7 , 39 41 Similarly, in larger mammalian eyes and humans, transport block in axons occurs in the connective tissue zone of the LC and myelination begins just posterior to this. 3 , 42 – 44 The accumulation of amyloid precursor protein 33 during axonal obstruction can lead to axonal swelling, 39 , 45 resulting in the increase in axonal area measured in this work.…”
Section: Discussionmentioning
confidence: 99%
“…46 Likewise, the axonal transport obstruction was barely detectable at 24 hours, but was significant at 3 days. 7 More than 1 week of IOP elevation led to substantial axonal degeneration and represented a different phase of the remodeling process. There were also large changes in strain response after 3 days of OHT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neurotrophic factors and neurotrophins have been used for RGC and axon survival 52 55 . Mitochondrial dysfunction as well as oxidative stress has been shown to contribute to RGC loss and axonal degeneration during injury 56 60 . The immune system also contributes to pathophysiology of glaucoma both in the retina and the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…As the main target of glaucoma, elevated IOP is associated with glaucomatous optic nerve damage and visual field loss. Kimball et al [ 32 ] found that IOP elevation in elder mice caused clear abnormalities in the density and movement of mitochondria as well as axonal integrity. The stability of IOP seems to be essential.…”
Section: Discussionmentioning
confidence: 99%